Transcranial direct current stimulation disrupts tactile perception - Rogalewski, Andreas; Breitenstein, Caterina; Nitsche, Michael A.; Paulus, Walter; Knecht, Stefan (The European journal of neuroscience, 2004)
The excitability of the cerebral cortex can be modulated by various transcranial stimulation techniques. Transcranial direct current stimulation (tDCS) offers the advantage of portable equipment and could, therefore, be used for ambulatory modulation of brain excitability. However, modulation of cortical excitability by tDCS has so far mostly been shown by indirect measures. Therefore, we examined whether tDCS has a direct behavioral/perceptional effect. We compared tactile discrimination of vibratory stimuli to the left ring finger prior to, during and after tDCS applied for 7 min at 1‐mA current intensity in 13 subjects. Stimulation was pseudorandomized into cathodal, anodal and sham conditions in a within‐subject design. The active electrode was placed over the corresponding somatosensory cortex at C4 according to the 10–20 EEG system and the reference electrode at the forehead above the contralateral orbita. Cathodal stimulation compared with sham induced a prolonged decrease of tactile discrimination, while anodal and sham stimulation did not. Thus, cortical processing can be modulated in a behaviorally/perceptually meaningful way by weak transcranial current stimulation applied through portable technology. This finding offers a new perspective for the treatment of conditions characterized by alterations of cortical excitability.